Sequential depletion of rat testicular lipids with long-chain and very long-chain polyenoic fatty acids after X-ray-induced interruption of spermatogenesis - Oresti, Gerardo Martin (2010)
When a single dose of X-rays is applied to the adult rat testis, stem spermatogonia are damaged and spermatogenesis is interrupted. Supported by Sertoli cells, those spermatogenic cells that endure irradiation complete their differentiation and gradually leave the testis as spermatozoa. In this study, the in vivo changes taking place a number of weeks after irradiation revealed cell-specific features of testicular lipid classes. A linear drop, taking about 6 weeks, in testis weight, non-lipid materials, free cholesterol and 22:5n-6-rich glycerophospholipids took place with germ cell depletion. Sphingomyelins and ceramides with non-hydroxy very long chain polyenoic fatty acids (n-VLCPUFA) disappeared in 4 weeks, together with the last spermatocytes, whereas species with 2-hydroxy VLCPUFA lasted for 6 weeks, disappearing with the last spermatids and spermatozoa. The amount per testis of 22:5n-6-rich triacylglycerols, unchanged for 4 weeks, fell between weeks 4-6, associating these lipids with spermatids and their residual bodies, detected as small bright lipid droplets. In contrast, 22:5n-6-rich species of cholesterol esters, and large lipid droplets, increased in seminiferous tubules up to week 6, revealing they are Sertoli cell products. At week 30, the lipid and fatty acid profiles reflected the resulting permanent testicular involution. Our data highlight the importance of Sertoli cells in maintaining lipid homeostasis during normal spermatogenesis.